Synthesis and structure of complex phosphates Na3,5MIІ 0,5Fe1,5(PO4)3 (MII — Mg, Ni), obtained under condition of the crystallization of multicomponent self-fluxes - Strutynska, N.Yu.; Spivak, A.V.; Baumer, V.N.; Slobodyanik, M.S. (Reports of the National Academy of Sciences of Ukraine, 2021)
The regularities of the formation of complex phosphates in the system Na2O—P2O5—Fe2O3—MIIO (MII — Co, Mg, Ni at the crystallization of multicomponent self-fluxes at the values of molar ratios: Na/P = 1,3, Fe/P = 0,3, Fe/MII = 2, over the temperature interval of 1000-650 °С have been investigated. The single crystals of complex phosphates of Na3,5MIІ0,5Fe1,5(PO4)3 (MII — Mg, Co, Ni) 5 mm in size have been grown. In the FTIR spectra of synthesized complex phosphates Na3,5MIІ0,5Fe1,5(PO4)3 (MII — Mg, Co, Ni), the characteristic modes in the regions of 900-1200 сm–1 (symmetric and asymmetric stretching vibrations (v4, v1, and v3) of a phosphate tetrahedron) and 400-600 сm–1 (corresponding deformation vibration) have been confirmed the presence of an orthophosphate–type anion in their composition. The calculated cell parameters for obtained phosphates (trigonal system, space group R-3c) are in the range of values (а, b) = 8,68 ÷ 8,80 Å and c = 21,47 ÷ 21,58 Å and depend on the nature of MII. The basic building block of the structure of complex phosphates Na3,5MIІ0,5Fe1,5(PO4)3 (MII — Mg, Co, Ni) is the [(MІІ/Fe)2 (PO4)3] unit, which consists of two (MІІ/Fe)O6 polyhedra interlinked by three bridging PO4-tetrahedra. The Na+ cations are distributed over two partially occupied sites in the cavities of the framework. The presence of vacancies in the cationic sublattice of complex phosphates with NASICONrelated structure will further affect the ion-conducting properties of solid electrolytes based on them.